Occupational Safety and Health Before Sailing on Fish Catchers in Lappa Sub-district, North Sinjai - Irfandi Rahman; Fatmawaty Mallapiang; Suharni Andi Fachrin; Hasriwiani Habo Abbas (Window of Health, 2019)
Fishermen fishing is a job on the surface of the water, where fishermen catching fish are at high risk of experiencing Accidents due to Work or Disease due to Work (Kalalo, 2016, Handayani, 2014, Tjahjanto, 2016, Purwanto, 2014, Putra, 2017, Purwangka, 2013). This study aims to examine the application of occupational safety to fishing fishermen in Lappa Village and examine the application of occupational health to fishing fishermen in Lappa Village. This study uses qualitative research methods with a phenomenological approach. The informants of this study were 6 people, with the criteria of fishing fishermen. The technique of collecting data uses in-depth interviews, document review, and observation. Research results show that work safety before going to sea (having experience and knowledge of the weather, praying, checking the condition of the boat and engine, safety equipment). While occupational health for fishing fishermen before going to sea (having a fishing card, knowing the functions and benefits of fishing cards, conducting a health check). Conclusion (1) important fishing fishermen prepare safety before going to sea. (2) fishing fishermen need to prepare medical devices such as first aid kits, fishermen cards, health education programs, and health units for fishing fishermen in Lappa Village, North Sinjai District, Sinjai District.